Hippocampal slow EEG frequencies during NREM sleep are involved in spatial memory consolidation in humans. Issue 10 (13th May 2014) - Moroni, Fabio; Nobili, Lino; Iaria, Giuseppe; Sartori, Ivana; Marzano, Cristina; Tempesta, Daniela; Proserpio, Paola; Lo Russo, Giorgio; Gozzo, Francesca; Cipolli, Carlo; De Gennaro, Luigi; Ferrara, Michele
ABSTRACT The hypothesis that sleep is instrumental in the process of memory consolidation is currently largely accepted. Hippocampal formation is involved in the acquisition of declarative memories and particularly of spatial memories. Nevertheless, although largely investigated in rodents, the relations between spatial memory and hippocampal EEG activity have been scarcely studied in humans. Aimed to evaluate the effects of spatial learning on human hippocampal sleep EEG activity, we recorded hippocampal Stereo‐EEG (SEEG) in a group of refractory epilepsy patients undergoing presurgical clinical evaluation, after a training on a spatial navigation task. We observed that hippocampal high‐delta (2–4 Hz range) activity increases during the first NREM episode after learning compared to the baseline night. Moreover, the amount of hippocampal NREM high‐delta power was correlated with task performance at retest. The effect involved only the hippocampal EEG frequencies inasmuch no differences were observed at the neocortical electrodes and in the traditional polysomnographic measures. The present findings support the crucial role of hippocampal slow EEG frequencies during sleep in the memory consolidation processes. More generally, together with previous results, they suggest that slow frequency rhythms are a fundamental characteristic of human hippocampal EEG during both sleep and wakefulness, and are related to the consolidation of different types of memories. © 2014 Wiley Periodicals, Inc.